Forgetting to Remember: Theorizing the Role of the Forgotten In the Production of Biblical Text and Tradition - Kemp, Jenna (Biblical interpretation, 2023)
This article examines Exod 34:11–17 by utilizing theory of cultural memory, enriched with theory of metaphor and allusion. As the author of a late text, the scribe responsible for this insertion remembers other various biblical texts via allusion, creating synthetic categories that are useful for carrying the texts forward in time. The synthesis occurs, however, not just by remembering but also by forgetting parts of the evoked texts. The fact that they can be read together strengthens the idea that multiple texts could be considered a conceptual whole. Forgetting is therefore not just about loss; it is as a result of loss extremely productive in creating and maintaining conceptual links between texts within the tradition.